Factores psicopedagógicos y su relación en el aprendizaje inicial de la lectoescritura de los niños y niñas del primer año de educación básica de la unidad educativa municipal Catamayo del cantón Catamayo. Periodo 2014 - Narvaez Bustos, Diana del Cisne (2015)
The present thesis titled to FACTORS PSICOPEDAGÒGICOS AND THEIR RELACIÒN IN THE INITIAL LEARNING OF LECTOESCRITURA OF THE CHILDREN AND GIRLS THE FIRST years old BÀSICA OF THE EDUCATIONAL "MUNICIPAL UNIT CATAMAYO" OF CANTÒN CATAMAYO. PERIOD 2014.Con this antecedent you objective specific plantearòn: To investigate if the factors psicopedagógicos have incidence in the lectoescritura of the children and girls of the Educational "Municipal Unit Catamayo." To establish the differences diagnoses as for the initial learning of the lectoescritura in function of the sex of the children and girls of the Educational "Municipal Unit Catamayo." To verify if the lectoescritura levels have relationship to the cultural variable level of the parents of the children's family and girls of the Educational "Municipal Unit Catamayo." The investigated population was confirmed by 26 children and girls, and 2 teachers. To carry out this investigative work several methods como: Scientific they were applied, Deductive, Inductive, Analytic Synthetic, Descriptive, Statistical. The techniques and used instruments were: the survey psicopedagógica was applied the teachers with the clear purpose of knowing the academic and human quality, aptitudes that will allow him/her to adapt the programming from the learning to each student's educational necessities, and a test of knowledge the same one that allowed me to verify the lectoescritura levels reached in the children and girls. After the analysis of the obtained information of educational and children you ended up concluding that of the 2 teachers parvularias of the Educational "Municipal Unit Catamayo" that represent 100% affirms that the factors psicopedagógicos impact directly in the initial learning of the lectoescritura, since they manifested that it is indispensable and opportune the attention psicopedagógica to the children from the beginning of its school stage, since this discipline studies each one of the human behaviors. According to the obtained results of the application of the conocimiento. De test the 26 children and investigated girls of the Educational "Municipal Unit Catamayo" that correspond to 100%; 22 children that are equal to 85% presented a Very Satisfactory level, while 4 children that correspond to 15% presented a Satisfactory level.